Penguatan Kemampuan Guru Membuat Modul Ajar Melalui Lokakarya Implementasi Kurikulum Merdeka di SD Sekolah Penggerak Kabupaten Lombok Timur - Hamidi Hamidi; Muhammad Hafizin; Sabahiyah Sabahiyah (Jurnal Pendidikan Dasar Flobamorata, 2023)
The purpose of this research is to provide reinforcement to the 2nd batch of Primary School teachers in the Mobilization School Program in East Lombok Regency. The type of research used is school action research. The method used in this activity is packaged through workshops on the implementation of the independent curriculum with 2 cycles. Data collection used observation techniques. Instruments include observation of participant activities, management observation, and evaluation of workshop products, namely teaching modules. The results of this research activity were (1) Participants' understanding of the independent curriculum teaching modules increased (2) Workshop activities greatly assisted teachers in creating or modifying teaching modules according to the potential and characteristics of each school. (3) It is hoped that there will be follow-up in the form of mentoring for similar activities carried out in schools other than driving schools